Antiretroviral therapy initiation alters the redox system of asymptomatic HIV-infected individuals: A longitudinal study - Tasca, Karen Ingrid [UNESP]; Caleffi, Juliana Trindade [UNESP]; Corrêa, Camila Renata [UNESP]; Gatto, Mariana [UNESP]; Tavares, Francilene Capel [UNESP]; Camargo, Caio Cavassan [UNESP]; Sartori, Alexandrina [UNESP]; Biasin, Mara; De Souza, Lenice Do Rosário [UNESP] (Wiley, 2017)
Background. The combination antiretroviral therapy (cART) increases the oxidative stress in HIV-infected people, which in turn favors the onset and aggravation of non-AIDS comorbidities, a common situation affecting these individuals. We aimed to evaluate the influence of cART initiation on oxidative stress parameters. This is a longitudinal study including 30 asymptomatic patients divided according to their CD4+ T cell count (G1: <500 cell/mL; G2: >500 cell/mL) before (M0) and after (M1) cART initiation. We analyzed total antioxidant capacity (TAC), fat-soluble vitamins, malondialdehyde, 8-isoprostane, and DNA damage. Results. Results showed a decrease in TAC, retinol, α-tocopherol, and some carotenoids, in addition to a significant increase in DNA damage at M1. These changes were more evident in G2 subjects. Moreover, there was a significant 8-isoprostane increase at M1 in individuals belonging to G1. Conclusion. The results indicate that cART interfered in the redox system, mainly by reducing the antioxidant defenses. In addition, patients who had CD4+ T counts higher than 500 cells/mm3 showed more susceptibility to genotoxicity, while patients with less CD4+ T counts displayed more damage triggered by lipoperoxidation. Considering the early beginning of cART, its chronic use, and its capacity to alter the redox status, further long-term studies on larger cohorts are needed to define the best time to initiate therapy and to investigate new strategies to delay the development of non-AIDS diseases.